Suppression of ferromagnetic order by Ag-doping: A neutron scattering investigation on Ce2(Pd1-xAgx)2In (x = 0.20, 0.50) - Martinelli, A. (2018)
The ground state magnetic behaviour of Ce2(Pd0.8Ag0.2)2In and Ce2(Pd0.5Ag0.5)2In, found in the ferromagnetic branch of Ce2Pd2In, has been investigated by neutron powder diffraction at low temperature. Ce2(Pd0.8Ag0.2)2In is characterized by a ferromagnetic structure with the Ce moments aligned along the c-axis and values of 0.96(2) μB. The compound retains the P4/mbm throughout the magnetic transition, although the magnetic ordering is accompanied by a significant decrease of the lattice strain along [0 0 l], suggesting a magnetostructural contribution. The magnetic behaviour of Ce2(Pd0.5Ag0.5)2In is very different; this compound exhibits an extremely reduced magnetic scattering contribution in the diffraction pattern, that can be ascribed to a different kind of ferromagnetic ordering, with extremely reduced magnetic moments (∼0.1 μB) aligned along [0 l 0]. These results point to a competition between different types of magnetic correlations induced by Ag-substitution, giving rise to a magnetically frustrated scenario in Ce2(Pd0.5Ag0.5)2In.